Inner and outer weather: Creative practice as contemplative ecological inquiry - Vasko, Zuzana (PRISM: Casting New Light on Learning, Theory and Practice, 2020)
Ecological crises exist not only in the external environment; they have their source within us — in the mind and in personal and cultural values (Bai, 2012; Stoknes, 2018).  Arts-based and contemplative inquiry are helpful in opening the self and the senses to the natural world and its elemental dynamics of weather. Creative contemplative practice also creates room for inner exploration about how we relate to other species and to the larger cosmos. This article describes a drawing project that was undertaken in an endeavour to build these connections, both within and without. Through the process of walking and making drawings of the bark of trees in a local ecosystem, attention was given also to the dynamics of weather and how we might be more conscious of its role in everyday life, with the belief that such caring attentiveness is necessary in a time of critical climate change. From a perspective that values interconnectivity, this exploration puts forth that the elements of air and water are within us too, and that our inner weather – our shifting psycho spiritual states – is affected by earth’s dynamics, just as, more importantly, and our more long-term values and psycho-spiritual perspectives have significant effects on ecological health.